Phallostethus cuulong, a new species of priapiumfish (Actinopterygii: Atheriniformes: Phallostethidae) from the Vietnamese Mekong - Shibukawa, Koichi; Tran, Dinh Dac; Tran, Loi Xuan (Zootaxa, 2012)
A new species of priapiumfish, Phallostethus cuulong, is described based on nine specimens collected from the Vietnam-ese Mekong. This is the third species of the genus, following the type species P. dunckeri (from Malay peninsula) and P.lehi (from northwestern Borneo), and distinguished from them by having: seven serrae on the second ctenactinium in adultmales (vs. five in P. dunckeri and eight in P. lehi); 25–26 caudal vertebrae (vs. 27 in P. dunckeri and 28 in P. lehi); approx-imately 5–19 teeth on paradentary (vs. 15–20 and 28 or more in P. dunckeri and P. lehi, respectively). All six examinedmales are dextral (vs. one and two known males are sinistral and dextral respectively in P. dunckeri, and all four knowmales are sinistral in P. lehi). Sexual dimorphism is also found in the number of precaudal vertebrae, i.e., 13–14 in males and 11–12 in females (vs. sexual dimorphism is not found in number of precaudal vertebrae of P. dunckeri and P. lehi).